Clinical features and outcomes of spitzoid proliferations in children and adolescents. (10th February 2019) - Bartenstein, D.W.; Fisher, J.M.; Stamoulis, C.; Weldon, C.; Huang, J.T.; Gellis, S.E.; Liang, M.G.; Schmidt, B.; Hawryluk, E.B.
Summary: Background: Spitzoid proliferations range from Spitz naevi to melanomas. There are few studies describing clinical features and outcomes in the paediatric population. Objectives: To determine the clinical features and outcomes of a large paediatric cohort with histopathologically confirmed Spitz tumours. Methods: This was a retrospective cohort study of patients seen at Boston Children's Hospital who were aged < 20 years and had a histopathological diagnosis of spitzoid proliferation from 1 January 1994 to 23 October 2012. Results: In total 595 patients with 622 spitzoid proliferations were identified (median age 7·4 years, interquartile range 4·6–11·7). Overall 512 proliferations (82·3%) were typical, 107 (17·2.%) were atypical and three (0·5%) were melanomas. The median ages at biopsy were 7·4, 7·2 and 17·2 years, respectively, and there was a significant difference in age at biopsy for patients with typical or atypical proliferations vs. melanoma ( P < 0·01). Among samples with positive margins ( n = 153), 55% (54 of 98) of typical proliferations, 77% (41 of 53) of atypical proliferations and 100% (two of two) of melanomas were re‐excised. Six patients had sentinel lymph node biopsy performed, with three patients demonstrating nodes positive for melanocytic cells. Within a median follow‐up of 4·1 years for the full cohort there were no related deaths. Conclusions: Spitz tumours have strikingly benign outcomes in the paediatric population, although this study is limited by the low number of melanomas and restriction to a single paediatric institution. Aggressive management recommendations should be reconsidered for children and adolescents with banal‐appearing Spitz naevi, based on the clinically indolent behaviour in this cohort. Abstract : What's already known about this topic? Spitz naevi, atypical Spitz tumours and Spitz melanomas are pigmented lesions that are challenging to diagnose in the paediatric population. Both dermoscopy and genetic tests fail to diagnose these proliferations definitively, and histopathology remains the gold standard. Whereas similar lesions in adults may have aggressive outcomes, paediatric‐specific data are limited. What does this study add? This study adds paediatric‐specific data from a large cohort, and current management practices are reviewed. With over two decades of data demonstrating benign clinical outcomes in children with biopsy‐proven lesions, clinical monitoring may be considered for banal‐appearing spitzoid proliferations in paediatric patients. Linked Editorial: Elder and Barnhil. Br J Dermatol 2019; 181 :235 . Plain language summary available online Respond to this article